Force and Slip Displacement of Fibre Cemboard Panels Subjected To Four-Point Bending Test - Mohammed, Nur Amirah; Norhalim, Arnie Farhana; Mohd Jaini, Zainorizuan; Abu Seman, Mazlan (International Journal of Integrated Engineering, 2022)
For many years, fibre cemboard has been widely used in the construction industry. This material has many advantages, including a long-life span, ease of installation and low maintenance. However, due to its limitation of being unable to support heavy loads, fibre cemboard is only suitable for the lightweight floor system. Therefore, fibre cemboard panels are introduced for heavy-duty facilities. Fibre cemboard panels comprise several layers of fibre cemboard that stack together using a specific bond mechanism. This study aims to investigate the force and slip displacement of fibre cemboard panels with different bond mechanisms (polyurethane glue, steel bolts and polyurethane glue + steel bolts) at various spacings (50 mm, 75 mm, 100 mm, 150 mm, and 200 mm). The specimens were fabricated with a size of 305 mm in width, 1220 mm in length and 2@16 mm in thickness. The four-point bending test was carried out using Universal Testing Machine (UTM) that yield the force-slip displacement curves. The results of experimental testing indicate that the bond mechanism has an apparent impact on the force and slip displacement. Overall, the fibre cemboard panels bonded by steel bolts have the best performance. The spacing was found to control the slip displacement the most than the force. Close distance of spacing increases the stiffness that appreciably contributes to the lower value of slip displacement. The optimum spacing for the fibre cemboard panels bonded by polyurethane glue, steel bolts, and polyurethane glue + steel bolts is 50 mm, 100 mm, and 150 mm, respectively. During the loaded phase, polyurethane glue can hold the stresses up until the detachment of fibre cemboard. When polyurethane glue fails, the steel bolts resume the function to resist the slip displacement until the rapture.